Hirsch and Brenner's atlas of EEG in critical care - Hirsch, Lawrence J.; Fong, Michael W. K. (Michael Wang Keong), 1985-; Brenner, Richard P. (Hoboken, NJ : Wiley-Blackwell, John Wiley & Sons, Ltd., 2023)
"Rapid diagnosis in the ICU is key to maximizing the patient's chances. EEG is a major diagnostic tool that can help determine extent of injury, any lesions and their location. Prolonged monitopring can provide better prognostic detail. But EEG traceouts are complex. Differences in brain states can be subtle. Recognizing the nuances quickly can be the key to providing the best help to your patient. Hirsch and Brenner's Atlas of EEG in Critical Care provides detailed exemplar traces that cover the situations you will find in the ICU. Key differentiating features are clearly highlighted in colour on the EEG traces. This book includes: The principles of EEG techniques and interpretation A wide range of neurologic conditions including encephalopathy, seizures, stroke, coma, mimics and artifacts The methods of data management and trending central to long-term monitoring Multi-modal monitoring correlating with techniques such as microdialysis Evoked and event-related potentials Atlas of EEG in Critical Care provides you with the EEG knowledge and skills you need for your patients wellbeing in the ICU"--
EEG basics -- Practical approach to the critical care EEG and its classification -- Encephalopathy and coma -- Focal EEG abnormalities -- Rhythmic and periodic patterns -- Seizures, status epilepticus and the ictal-interictal continuum -- Artifacts that can mimic seizures or other physiologic patterns -- Post cardiac arrest patterns -- Quantitative EEG : basics, seizure detection, and avoiding pitfalls -- Quantitative EEG special applications and multimodal monitoring
Title page mentions "Second Edition Edited By" but no other contributors listed
Preceded by Atlas of EEG in critical care / Lawrence J. Hirsch, Richard P. Brenner. c2010
Keywords: Electroencephalography -- Methods; Critical care medicine; Electroencephalography -- methods; Critical Care; Atlas